2013
DOI: 10.1007/s10554-013-0344-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pulmonary computed tomography angiography: a new standard for evaluation of combined airway and vascular abnormalities in infants

Abstract: Airway abnormalities are frequently associated with congenital heart disease in infants and children. Respiratory distress in these children frequently requires prolonged respiratory support. Wide-detector dynamic pulmonary computed tomography angiography (DP-CTA) is a non-invasive technique that completely evaluates vascular and airway abnormalities during a single breathe. Our purpose was to evaluate the efficacy of DP-CTA to provide unique actionable information for patient care in newborns and infants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 18 publications
1
54
0
Order By: Relevance
“…Flexible bronchoscopy can allow assessment of a more natural airway, as airway stenting does not occur, and it can be used to assess for distal pathologies [13]. result of a dynamic cine pulmonary CT [27]. Gaarfar concludes that CTA is necessary in children with a high level of suspicion of vascular anomaly [28] and the current study would support this recommendation.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 54%
“…Flexible bronchoscopy can allow assessment of a more natural airway, as airway stenting does not occur, and it can be used to assess for distal pathologies [13]. result of a dynamic cine pulmonary CT [27]. Gaarfar concludes that CTA is necessary in children with a high level of suspicion of vascular anomaly [28] and the current study would support this recommendation.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 54%
“…However, patients included in that study suffered from very severe TBM in whom surgery was required, so this was a biased population and the accuracy of the MDCT scan may have been overestimated [9]. Free-breathing cine-MDCT is an alternative technique in young children as it does not require general anaesthesia and controlled ventilation, and radiation exposure is low (mean effective dose <2 mSv, with the minimum ever reported 0.19-0.8 mSv) [11][12][13]. Reported sensitivity (96.3%) and specificity (97.2%) are high compared with bronchoscopic evaluation [11].…”
Section: Multidetector Computed Tomographymentioning
confidence: 99%
“…Another concern is the need for sedation and intubation in younger children, which can distort the airway and change the tracheal dynamics [7,9,11,12,28]. This problem can be partially solved by using free-breathing cine-MDCT [11][12][13].…”
Section: Multidetector Computed Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Aided by sedation or anesthesia, we are now able to routinely acquire motionless images of the tracheobronchial tree at full inspiration and end-expiration [42] in a cross-sectional format [17][18][19]43]; however these acquisitions do not truly investigate the dynamic nature of tracheo-bronchomalacia. To address this, others have developed free-breathing cine chest CT [44,45] and "four-dimensional" CT on a scanner with enough detectors to cover the relevant anatomy without need for table motion [9,[46][47][48][49]. Yet, I have found that my results with these techniques usually did not affect the clinical management of dynamic airway collapse because most children eventually outgrow this condition and bronchoscopy has remained the diagnostic gold standard for this condition at my hospital [50].…”
mentioning
confidence: 99%